Apakah Koneksi Politik Mempengaruhi Pengungkapan Lingkungan? - Yeterina Nugrahanti; Debbie Natasya (Universitas Muhammadiyah Malang, 2023)
Purpose: This research aims to determine the influence of political connections, company size and company age on environmental disclosure in manufacturing companies listed on the IDX in 2020-2021, either simultaneously or partially, by using company size and company age as control variables.. Methodology/approach: This research uses quantitative methods through a sampling approach, obtaining 99 companies with 198 data. Using multiple linear regression analysis. Data processing was carried out using SPSS Statistics 25. Findings: The results of this study indicate that political connections and company size have a significant positive impact on corporate environmental disclosure. However, company age does not have a significant impact on environmental disclosure. Practical and Theoritical contributio/Origanlity: This research provides knowledge about political connections, company size and company age for environmental disclosure of manufacturing sector companies in 2020-2021. The implication is that companies use environmental disclosure to generate good relations with the government and are expected to increase positive views of the company and attract investors to invest. Research Limitation: This research is still limited to the scope of the research sample for a research period of two years so that the results do not reflect the long-term situation. In addition, it does not discuss the quality of environmental disclosure items disclosed by the company.